Avaliação da atividade genotóxica e antigenotóxica de Celtis iguanaea (Jacq.) Sargent em bactérias e camundongos - Borges, Flávio Fernandes Veloso (2010)
Celtis iguanaea (Jacq.) Sargent is a member of the Cannabaceae family and popularly known as esporão de galo. Ethnobotanical surveys of cerrado native plants show that the tea leaves of C. iguanaea is used in traditional medicine for body aches, asthma, cramps, poor digestion, urinary infections, kidney disfunctions, as a stimulant or as a diuretic.The purpose of the present work was to evaluate the possible cytotoxic, genotoxic and antigenotoxic effects of the leaves aqueous extract of C. iguanaea by the prophage λ induction test (SOS Inductest) and the micronucleous test in mice bone marrow. The SOS Inductest was performed according to Moreau (1976), using lysogenic WP2s(λ) and indicator RJF013 strains derived from Escherichia coli. WP2s(λ) cultures were treated with different doses of the extract (0.5, 1, 2.5, and 5 mg) (evaluation of genotoxicity) or co-treated with a single dose of MMC (0,5 mg) and different doses of extract (assessment of antigenotoxicity). Then, the treated culture was added to the indicator strain (RJF013) and both were poured on plates in LB(1/2) medium. For the evaluation of cytotoxicity, cultures of WP2s(λ) treated with different doses of extract were diluted in M9 buffer and plated on LB. The micronucleus test was carried out according to Schmid (1975). To assess the genotoxic activity, animals were treated with Celtis iguanaea extract (100, 300 and 500 mg/kg concentrations). To evaluate the antigenotoxic activity, the same doses of extract were treated simultaneously with 4mg/Kg of MMC. The frequencies of micronucleated polychromatic erythrocytes (MNPCE) were evaluated at 24h and 48h exposure period except the negative control (24h). The cytotoxicity was assessed by the polychromatic and normochromatic erythrocytes ratio (PCE/NCE). In both tests the obtained results demonstrated anticytotoxic activity and absence of genotoxicity and cytotoxicity of the Celtis iguanaea leaves extract. The extract also showed partial antigenotoxic activity in bacteria and antigenotoxic activity in mice.